2011
DOI: 10.1538/expanim.60.79
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Internal Fixator Stiffness on Murine Fracture Healing: Two Types of Fracture Healing Lead to Two Distinct Cellular Events and FGF-2 Expressions

Abstract: This study aimed to clarify the relationship between the mechanical environment at the fracture site and endogenous fibroblast growth factor-2 (FGF-2). We compared two types of fracture healing with different callus formations and cellular events using MouseFix™ plate fixation systems for murine fracture models. Left femoral fractures were induced in 72 ten-week-old mice and then fixed with a flexible (Group F) or rigid (Group R) Mouse Fix™ plate. Mice were sacrificed on days 3, 5, 7, 10, 14, and 21. The callu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 30 publications
2
32
0
Order By: Relevance
“…here, GFPpositive cells were clearly observed in the fracture gap and callus, and were positive for aLP and type i collagen staining on day 7. by day 14, GFP-positive cells were observed around the callus and under the periosteum, in concurrence with the aLP and type i collagen staining. Moreover, von Kossa-positive cells were observed on day 14. in our previous studies, similar cellular events were observed within the same time period in wild-type c57bL/6J mice and a GFP bone marrow chimeric mouse [24,25]. taken together, our results suggest that bone marrow-engrafted Ucbcs contribute to fracture healing in a manner similar to endogenous bone marrow-derived cells.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…here, GFPpositive cells were clearly observed in the fracture gap and callus, and were positive for aLP and type i collagen staining on day 7. by day 14, GFP-positive cells were observed around the callus and under the periosteum, in concurrence with the aLP and type i collagen staining. Moreover, von Kossa-positive cells were observed on day 14. in our previous studies, similar cellular events were observed within the same time period in wild-type c57bL/6J mice and a GFP bone marrow chimeric mouse [24,25]. taken together, our results suggest that bone marrow-engrafted Ucbcs contribute to fracture healing in a manner similar to endogenous bone marrow-derived cells.…”
Section: Discussionsupporting
confidence: 88%
“…We used a rigid plate of the MouseFix tM system (ao development institute, davos, switzerland), which is a locking plate system with good angular stability, as an internal fixator of fractured mouse femurs [25]. Prior to the plate implantation and fracture of femurs, a mixture of 1 part midazolam (sandoz, tokyo, Japan), 3 parts domitor tM (nippon Zenyaku Kogyo co., Ltd., Fukushima, Japan), and 1 part Vetorphale tM (Meiji seika Pharma co., Ltd., tokyo, Japan) was intramuscularly injected into the upper limbs of mice at an optimal dose of 0.05 ml/100 g to induce anesthesia.…”
Section: Creation Of a Mouse Fracture Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…1B) configuration. We have already confirmed that we can observe two distinct cellular events at the fracture healing site using two Mouse Fix™ plates with different levels of flexibility [24]. By the same technique, a mixture of 1 part midazolam, 3 parts Domitor™, and 1 part Vetorphale™ was then intramuscularly injected into the upper limbs at an optimal dose of 0.05 ml/100 g. The operation was performed only on the left femur.…”
Section: Creation Of the Fracturementioning
confidence: 58%
“…We already reported that the use of different types of plates with the Mouse Fix™ system leads to 2 different types of fracture healing, with differences in the type of callus formation and cellular events [10,24].…”
Section: Introductionmentioning
confidence: 99%